Investigation of the Phase Composition of Samples Sintered from Tungsten-containing Composite Micro - and Nanopowders - E.V. Ageev; A.Y. Altukhov; S.V. Khardikov (Журнал нано- та електронної фізики)
Presents the results of research of phase composition of samples sintered from tungsten-containing composite micro- and nano-powders obtained by mixing a powder VK8 (70 %) and PRS powder (30 %) obtained in kerosene lighting. It is established that the main phase of the sintered sample are the WC and Fe3С.